EFFECT OF NIACIN SUPPLEMENTATION AND WATER SPRAYING IN SOME REPRODUCTIVE TRAITS FOR FRIESIAN COWS UNDER - Dhafer SH. ALDoori (Mesopotamia Journal of Agriculture)
This study was conducted in AL-Ishaqi Cattle Station, north of Baghdad, 36 multifarious Friesian cows used in her early productive season, cows were divided randomly into two main groups (18 for each) spraying and without spraying group and Each group was divided into three sub-groups gives niacin (0 ,6 ,12g/day/cow) for the period from 1/6/2010 to31/7/2011 to study the effect of niacin supplementation and spraying water in numbers of services per conception, days open, fertility rate, period between calving , and abortions% , the results showed influenced fertility rate and abortions significantly )P ≤ 0.01) with niacin supplementation, and influenced number of services per conception and the period between calving significantly )P ≤ 0.05) with niacin supplementation as the rate of the first character 2.50 inseminated versus 3.50 inseminated and the rate of the second character 412.14 day versus 442 day while not record significant effect of niacin on days open, also no record of spraying impact on these traits .